Biochemical characterization of peptides from herpes simplex virus glycoprotein gC: loss of CNBr fragments from the carboxy terminus of truncated, secreted gC molecules. - Kikuchi, G E (1984)
A biochemical characterization of peptides from herpes simplex virus type 1 glycoprotein gC was carried out. We utilized simple micromethods, based on immunological isolation of biosynthetically radiolabeled gC, to obtain gC in pure form for biochemical study. CNBr fragments of gC were prepared, isolated, and characterized. These CNBr fragments were resolved into six peaks by chromatography on Sephacryl S-200 in 6 M guanidine hydrochloride. Only three of the CNBr fragments contained carbohydrate side chains, as judged from the incorporation of [14C]glucosamine. Radiochemical microsequence analyses were carried out on the gC molecule and on each of the CNBr fragments of gC. A comparison of this amino acid sequence data with the amino acid sequence predicted from the DNA sequence of the gC gene showed that the first 25 residues of the predicted sequence are not present in the gC molecule isolated from infected cells and allowed alignment of the CNBr fragments in the gC molecule. Glycoprotein gC was also examined from three gC mutants, synLD70, gC-8, and gC-49. These mutants lack an immunoreactive envelope form of gC but produce a secreted, truncated gC gene product. Glycoprotein gC from cells infected with any of these gC- mutants was shown to have lost more than one CNBr fragment present in the wild-type gC molecule. The missing fragments included the one containing the putative transmembrane anchor sequence. Glycoprotein gC from the gC-8 mutant was also shown, by tryptic peptide map analysis, to have lost more than five major arginine-labeled tryptic peptides arginine-labeled tryptic peptides present in the wild-type gC molecule and to have gained a lysine-labeled tryptic peptide not present in wild-type gC.